Investigation of a super performance dew point air cooler and its application in buildings - Xu, Peng (2017)
Based on extensive literature reviews, technical opportunities were identified to improve the energy efficiency of a dew point air cooler. This applied research aimed to develop a super-performance dew point air cooler to replace or partly replace the conventional energy-intensive air conditioners applicable to buildings. This research followed the methodology of combined theoretical and experimental investigation and a procedure of concept formation, validating and updating. A simulation software was developed and validated to investigate the impacts of the geometric configuration and operational conditions on the unit’s cooling performance and assist the prototype design. As a result, a novel dew point air cooler prototype, featuring innovative structure of the heat and mass exchanger, application of new materials and new processes, unique water distribution and control scheme and exclusive self-developed simulation software, was constructed and tested under controlled laboratory environment. Two patents were generated, one of which has been authorized by the China State Intellectual Property Office and the other has been filed in the Intellectual Property Office of the United Kingdom. Under standard testing conditions, i.e. dry-bulb temperature of 37.8oC and the coincident wet-bulb temperature of 21.1oC, the prototype cooler achieved a wet-bulb cooling effectiveness of 114% and dew-point cooling effectiveness of 75%, yielding a significantly high Coefficient of Performance (COP) of 52.5 at the optimal working air ratio of 0.364. The performance testing was also carried out under various simulated conditions representing the climates of hot & dry, warm & dry, moderate, warm & humid and the wet-bulb effectiveness of the prototype kept in the range 112% to 128% and dew-point effectiveness of 67%-76%, giving a COP of 37.4-52.5. Compared to the conventional vapour compression air conditioners which have a COP of around 3, the prototype cooler had 11-17 times higher COP, leading to a reduction in electrical power consumption by around 92% to 94%. A dedicated case study of the proposed dew point cooler based on conditions in Beijing, a representative city in warm and humid climate, was carried out to predict the annual operational performance, economic rewards, and associated environmental benefits. Compared to the conventional packaged air conditioners, 91.4% of annual power demand could be saved. The annual water consumption is less than 0.3 tonnes to provide the cooling of 2428.1 kWh. And the payback period of static investments would be less than 4 years to replace an equivalent packaged air conditioner. A significant leap forward has been achieved with this study and this is expected to open enormous global business in the very near future, thus bringing about great economic, environmental and sustainability benefits worldwide.
HydraID: hull:16481 Hydra Discover Access Group: public ETD Collection: ETDEngineering
Keywords: Engineering